2010
DOI: 10.1029/2009ja014452
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of chorus in the outer dayside magnetosphere

Abstract: [1] Using ELF/VLF wave data recorded in 2007 from two high-latitude (L = 69.8°, 71.8°) Antarctic ground stations, the dayside variation of chorus wave occurrence and amplitude are analyzed in conjunction with geomagnetic and solar wind driving parameters. Both stations observe chorus (defined here as discrete rising emission tones together with unstructured hiss) in a broad window of local time across the dayside when the stations are on closed magnetic field lines. Wave occurrence rates rise rapidly from ∼0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 53 publications
9
45
0
Order By: Relevance
“…Waves on the dayside occur over a wider range of activity, and even during quiet conditions wave mean and time‐averaged amplitudes at noon significantly exceed disturbance amplitudes at midnight (at least at latitudes of >15°). High occurrence in the noon sector is not fully understood [ Tsurutani et al , 2009; Santolík et al , 2010; Sigsbee et al , 2010; Spasojevic and Inan , 2010] but is likely a combination of several factors including higher magnetic field homogeneity and lower damping leading to superior generation or propagation conditions as well as additional contributions to chorus source energy aside from injected electrons. It has been suggested that this could be related to the local magnetospheric configuration because of solar wind speed or dynamic pressure [e.g., Tsurutani and Smith , 1977; Koons and Roeder , 1990; Santolík et al , 2005b; Li et al , 2009; Spasojevic and Inan , 2010].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waves on the dayside occur over a wider range of activity, and even during quiet conditions wave mean and time‐averaged amplitudes at noon significantly exceed disturbance amplitudes at midnight (at least at latitudes of >15°). High occurrence in the noon sector is not fully understood [ Tsurutani et al , 2009; Santolík et al , 2010; Sigsbee et al , 2010; Spasojevic and Inan , 2010] but is likely a combination of several factors including higher magnetic field homogeneity and lower damping leading to superior generation or propagation conditions as well as additional contributions to chorus source energy aside from injected electrons. It has been suggested that this could be related to the local magnetospheric configuration because of solar wind speed or dynamic pressure [e.g., Tsurutani and Smith , 1977; Koons and Roeder , 1990; Santolík et al , 2005b; Li et al , 2009; Spasojevic and Inan , 2010].…”
Section: Discussionmentioning
confidence: 99%
“…High occurrence in the noon sector is not fully understood [ Tsurutani et al , 2009; Santolík et al , 2010; Sigsbee et al , 2010; Spasojevic and Inan , 2010] but is likely a combination of several factors including higher magnetic field homogeneity and lower damping leading to superior generation or propagation conditions as well as additional contributions to chorus source energy aside from injected electrons. It has been suggested that this could be related to the local magnetospheric configuration because of solar wind speed or dynamic pressure [e.g., Tsurutani and Smith , 1977; Koons and Roeder , 1990; Santolík et al , 2005b; Li et al , 2009; Spasojevic and Inan , 2010]. Recent studies have shown that particles experiencing so‐called Shabansky orbits, in which their drift motion shifts to high latitudes in the outer dayside [ Shabansky , 1971], can lead to significant ion anisotropies and subsequently ion cyclotron wave growth in this region [ McCollough et al , 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these modes could be responsible for non-ducted electromagnetic wave propagation in the low-band range (Lauben et al, 2002;Helliwell, 1995). There is observational evidence that electromagnetic waves originated in the outer region of the Earth's dayside magnetosphere can propagate to the ground (Spasojevic et al, 2008). It is possible that Gendrin mode waves may be responsible for these ground observations and we suggest that further modeling efforts be undertaken to determine if this is the correct interpretation or not.…”
Section: Discussionmentioning
confidence: 99%
“…Chorus waves on the dayside, on the other hand, have a relatively high overall occurrence probability compared with other magnetospheric regions [ Tsurutani and Smith , 1977; Sigsbee et al , 2010; Li et al , 2011a] and show little dependence of occurrence on geomagnetic activity [ Tsurutani and Smith , 1977; Spasojević and Inan , 2010]. Dayside chorus has been observed over a wider range of magnetic latitudes (extending at least 25° off the equator) [e.g., Burton and Holzer , 1974; Tsurutani and Smith , 1977; Meredith et al , 2001a; Vaivads et al , 2007; Tsurutani et al , 2009].…”
Section: Introductionmentioning
confidence: 99%